Oxidation and associated pore structure modification during experimental alteration of granite. (1st January 2021) - Anovitz, Lawrence M.; Cheshire, Michael C.; Hermann, Raphael P.; Gu, Xin; Sheets, Julia M.; Brantley, Susan L.; Cole, David R.; Ilton, Eugene S.; Mildner, David F.R.; Gagnon, Cedric; Allard, Lawrence F.; Littrell, Kenneth C.
Abstract: Weathering plays a crucial role in a number of environmental processes, and the microstructure and evolution of multi-scale pore space is a critically important factor in weathering. In igneous rocks the infiltration of meteoric water into initially relatively dry material can initiate disaggregation, increasing porosity and surface area, and allowing further disaggregation and weathering. These processes, in turn, allow biota to colonize the rock, further enhancing the weathering rate. In some rocks this may be driven by primary mineral oxidation. One such mineral, biotite, has been repeatedly mentioned as a cause of cracking during oxidation. However, the scale-dependence of the processes by which this occurs are poorly understood. We cannot, therefore, accurately extrapolate laboratory reaction rates to the field in predictive numerical models. In order to better understand the effects of oxidation and test the hypothesis that fracture and disaggregation are initiated by swelling of oxidizing biotites, we reacted granite cores in a selenic acid-rich aqueous solution at 200  °C for up to 438  days. Elevated temperatures and selenic acid were used to provide relatively fast reaction rates and highly oxidizing conditions in sealed reaction vessels. These experiments were analyzed using a combination of imaging, X-ray diffraction, Mössbauer spectroscopy, and small- and ultra-small angle neutron scattering to interrogate porosity and microfracture formation. The experimental results show little observable biotite swelling, but significantly more observable fractures and growth of iron oxides and/or clays along grain boundaries. Pyrite disappeared from the reacted sample. Significant increases in porosity were also observed at the sample rim, likely associated with feldspar alteration. Fractures and transport were observed throughout the core, suggesting that stresses due to crystallization pressures caused by the growing iron phases may be the initiating factors in granite weathering, possibly followed by biotite swelling after sufficient permeability is achieved.